The Optimization of the Role of Correctional Centers in the Indonesian Criminal Justice System - Muhammad Arif Agus; Ari Susanto (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
The purpose of this research is to examine and analyze (1) the role of Correctional Centers in the Criminal Justice System in Indonesia; and (2) the Optimization of the Role of Correctional Centers in the Criminal Justice System in Indonesia. The research method used is a normative juridical approach. The results of the research concluded; (1) Correctional Centers in the juvenile criminal justice system and in the adult criminal justice system both have a role, but the role of Correctional Centers in the adult criminal justice system has not been optimized as in the juvenile criminal justice system, and it tends to be discriminatory. (2) The optimization of the role of Correctional Centers in the Criminal Justice System in Indonesia needs to be carried out, because by optimizing the role of Correctional Centers, especially Correctional Research on adult cases, it will eliminate discrimination in treatment between children and adults and Correctional Research can be used as a reference for law enforcers. As a recommendation, it is suggested that in the Criminal Law Reform in Indonesia, both related to the renewal of the Criminal Procedure Law Code (KUHAP); the Criminal Code (KUHP); as well as the Corrections Law, the discrimination in making Correctional Research on juvenile cases and adult cases should be abolished, because it has no value of justice. The equalization of treatment related to Correctional Research will optimize the role of Correctional Research and also other law enforcers in achieving the value of justice in Indonesia.